Smart Driving in Smart City - Karaduman, Mucahit; Eren, Haluk (Ieee, 2017)
Smart cities have been drawing attention of researchers as seen in recent intensive studies. In associated with this fact, this situation is expected to continue in future works. In other side, smart vehicles are an indispensable part of smart cities. Scientists have been researching vehicles and transportation in order to reach safe and comfortable mobility. Among these vehicles, cars are the first ones that affect human life. In this study, smart cars and their drivers are elaborated in behavioral aspect. Existing works have been discussed to figure out futuristic driving behavior in smart city environment. In order to understand human thought system, additional studies have been given and recommendations have been provided. As seen in the researches conducted in recent years, researchers have been tried to interpret behavior of drivers by examining data taken by smart phones and vehicle OBD output. Evaluations are conducted by result of the specified methods. In recent decade, it has been observed that these behaviors are not only estimations; but also systems mounted on vehicles learn overall driving behavior. Hence, developed systems should work online while drivers on steering wheel. Consequently, this study will enlighten existing trends for different types of learning schemes. Future studies are expected to combine car, driver's biologic, psychological, and environmental data. Thus, in the near future, systems that understand the human thought will be developed.
5th International Istanbul Smart Grid and Cities Congress and Fair (ICSG) -- APR 19-21, 2017 -- Istanbul, TURKEY
Keywords: Smart driving; incremental learning; driver behavior; online learning; smartphone sensors